Passive components limit the cost reduction of conventionally designed vanadium redox flow batteries. (November 2018) - Lüth, Thomas; König, Sebastian; Suriyah, Michael; Leibfried, Thomas
Abstract: A superior scalability and low energy-related costs promote flow batteries to be a promising large-scale storage technology. To date however, flow batteries struggle to compete with lithium-based batteries regarding system costs. To identify costs which are susceptible by the flow battery industry, we study the technology's value chain by breaking down the costs. The main components of a flow battery system are illustrated in Figure 1. The highlighted components are "off-the-shelf" components which are not exclusively made for flow batteries. Hence, the flow battery industry will hardly influence the price of these components, because they are already manufactured in large numbers. Our key finding is that regarding power-related costs, the conventional stack technology is at its limits. Lower electrolyte costs positively affect the system costs. However, to undercut today's prices of lithium-based systems only by reducing electrolyte costs, a much longer storage time than requested by today's business models is required. Hence, the power-related costs have to decrease. We show that new technologies, such as fully welded or clued stacks without using metal framing can dramatically reduce these costs. Furthermore, emphasis should be put on the control system. A programmable logic controller (PLC) is too expensive for small and medium scale energy storage systems. Hence, a more cost-efficient, smarter control system, comparable to the one used for balancing Lithium-based batteries, has to be developed.